Effect of Fiber Optic Chromatic Dispersion on the Performance of Analog Optical Link with External Modulation Aiming at Aerospace Applications - Ferreira Júnior,Antonio Alves (2013)
ABSTRACT: This paper addresses the subject of fiber optic chromatic dispersion effect on the performance of analog optical link with dual-drive electro-optic Mach-Zehnder modulator, aiming at aerospace applications. Thus, a direct detection link model that emphasizes both the modulator electronic drive and the dispersion characteristic of a linear optical fiber is discussed. Furthermore, a mathematical approach yielding a rather insightful analysis of the link performance for either optical double or single sideband modulation formats is fully discussed. It is worthwhile to point out that such modeling has the special feature of relying on a uniform nomenclature, which enables one to quickly retrieve a wide range of known results regarding optical fiber link performance that are already available on an ample literature. The model usefulness is illustrated by predicting the performance dependence of a direct detection fiber optic link with respect to the radiofrequency and link length. Results of numerical simulations for a link that comprises commercial optoelectronic components with potential for practical application on electronic warfare field were also provided.